Torsion and bending loads on a ski-touring boot shell during uphill and downhill skiing - Zullo, G.; Cibin, P.; Petrone, N. (Sports Engineering, 2023)
Ski touring is an established winter activity that has experienced a recent increase in popularity. Differently to alpine skiing, skier gains altitude without lifts, thus equipment weight must be minimized. Nevertheless, structural properties of the equipment, such as ski boots, must be adequate to withstand skiing loads. Several studies provided data on flexural stiffness of alpine ski boots in bench and field tests. The present study focused on the torsional properties of ski-touring boots. Indeed, touring bindings design implies a higher torque transmission to the front piece which induces a torsional load throughout the shell. To conduct the study, we prepared a ski-touring boot with strain gage bridges, and we performed bench tests to determine the stiffness of the boot and the bridge sensitivity. We also positioned and calibrated strain gage bridges to measure bending load in the shell and axial load in the ski/walk lever placed between shell and cuff of the boot. Then, we conducted a field test measuring the loads during a ski-touring trip including ascent and descent. Bench tests evidenced linearity of the torsion sensor, and a variation of stiffness depending on dummy leg absence/presence and boot buckle setting. Field tests showed torque ranges of 17 Nm in climbing and of 27 Nm in skiing. Bending moment range on the boot shell was of 150 and 228 Nm, respectively. Maximum force on the ski/walk mechanism reached 570 N. Results could be useful to test ski-touring boot performances and to optimize their design.